Phases, microstructure and mechanical properties of AlxCoCrFeNi high-entropy alloys at elevated temperatures - Wang, Woei-Ren; Wang, Wei-Lin; Yeh, Jien-Wei (Journal of alloys and compounds, 2014)
•Disordered BCC phase in Al0.9–Al1.0 alloys transforms into FCC and σ phases at 873K.•FCC and σ phases form in an associated manner from the Fe,Cr-rich BCC phase.•The σ phase connected with the FCC phase are formed from disordered BCC phase.•The TT range of the Alx alloys is at 810–930K which is about 0.5Tm of the alloys.•The Alx alloys with x⩾0.5 is slip below the TT and creep deformation above the TT. The Alx–Co–Cr–Fe–Ni high-entropy alloy system (x=0–1.8 in molar ratio) was prepared by vacuum arc melting and casting method. Variations of temperature on crystal structure, microstructure and mechanical properties were investigated. The evolution of structure with temperature can be classified into four types: Al0–Al0.3: FCC structure; Al0.5–Al0.7: mixed structure (FCC+spinodal A2+B2)→FCC+B2 structure; Al0.9–Al1.2: spinodal A2+B2 structure (<873K)→FCC+σ+B2 structure (⩾873K)→FCC+B2 structure (⩾1235K); and Al1.5–Al1.8: spinodal A2+B2 structure→B2 structure. The hot hardness transition temperature (TT) range of this alloy system was at 810–930K. The Al0.5 alloy exhibited the highest TT/Tm value. Above TT, the Al0 and Al0.3 alloys possessed the highest softening coefficient and the Al0.9 and Al1.0 alloys exhibited the maximum softening coefficient amongst the Alx alloys. Differences of constituent phases, phase distribution and morphology could account for the softening difference. The mechanism for high softening resistance was also discussed.